Naloxone Alleviate the Severity of Delirium in Hospitalized Patients With Parkinsonism: Three Case Reports - Jin, Haiyan; Zhang, Jie; Hu, Qiongyue; Ping, Junjiao; Jiang, Tingyun; Du, Baoguo; Duan, Xin (Frontiers in Psychiatry, 2021)
Purpose: Delirium is common in geriatric with Parkinson's disease (PD). Treatments for delirium have generally been neuroleptics; however, antipsychotics have potential effect to block striatal dopamine D2 receptors and worsen symptom of parkinsonism. We explored whether naloxone can alleviate delirium in PD and other forms of parkinsonism. Patients and Methods: Patients with parkinsonism who met the delirium criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) received naloxone infusions once or twice daily. Treatment effects were evaluated by the delirium rating scale–revised 98 (DRS-R98), including non-cognitive and cognitive subscales; the Richmond agitation–sedation scale (RASS); and the mini mental status examination (MMSE). Results: Two patients with primary parkinsonism, one with vascular PD were observed. The daily dose of naloxone was 2.08 ± 0.64 mg (range: 1–4 mg). Medication time last from 1 h to 7 days without side effects observed. Following with naloxone infusions, DRS-R98 scores decreased within 12 h and MMSE scores increased. The psychotic symptoms, disorientation, and attention deficits were alleviated significantly, while RASS scores decreased with naloxone treatment. Conclusion: Naloxone alleviated psychotic symptoms, improved cognitive dysfunction, and irritability in patients with delirium in the context of PD. The preliminary findings point out that the opioid system may be involved in the pathophysiology of delirium, which may be one of potential treat targets for delirium of PD.